Surveillance of ARV safety in pregnancy and breastfeeding: towards a new framework. (19th July 2022) - Renaud, Françoise; Mofenson, Lynne M.; Bakker, Charlotte; Dolk, Helen; Leroy, Valeriane; Namiba, Angelina; Sahin, Leyla; Shapiro, Roger; Slogrove, Amy; Thorne, Claire; Vicari, Marissa; Low‐Beer, Daniel; et al.
Abstract: Introduction: As new antiretrovirals (ARVs), including long‐acting ARVs for treatment and prevention, are approved and introduced, surveillance during pregnancy must become the safety net for evaluating birth outcomes, especially those that are rare and require large numbers of observations. Historically, drug pharmacovigilance in pregnancy has been limited and fragmented between different data sources, resulting in inadequate data to assess risk. The International Maternal Pediatric Adolescent AIDS Clinical Trials Network and World Health Organization convened a Workshop which reviewed strengths and weaknesses of existing programs and discussed an improved framework to integrate existing safety data sources and promote harmonization and digitalization. Discussion: This paper highlights that although robust sources of safety data and surveillance programs exist, key challenges remain, including unknown denominators, reporting bias, under‐reporting (e.g. in voluntary registries), few data sources from resource‐limited settings (most are in North America and Europe), incomplete or inaccurate data (e.g. within routine medical records). However, recent experiences (e.g. with safety signals) and current innovations (e.g. electronic record use in resource‐limited settings and defining adverse outcomes) provide momentum and building blocks for a new framework for active surveillance of ARV safety in pregnancy. A public health approach should be taken using data from existing sources, including registries of pregnancy ARV exposure and birth defects; observational surveillance and cohort studies; clinical trials; and real‐world databases. Key facilitators are harmonization and standardization of outcomes, sharing of materials and tools, and data linkages between programs. Other key facilitators include the development of guidance to estimate sample size and duration of surveillance, ensuring strategic geographic diversity, bringing partners together to share information and engaging the community of women living with HIV. Conclusions: Looking ahead, critical steps to safely introduce new ARVs include (1) adopting harmonized standards for measuring adverse maternal, birth and infant outcomes; (2) establishing surveillance centres of excellence in areas with high HIV prevalence with harmonized data collection and optimized electronic health records linking maternal/infant data; and (3) creating targets and evaluation goals for reporting progress on implementation and quality of surveillance in pregnancy. The platform will be leveraged to ensure that appropriate contributions and strategic actions by relevant stakeholders are implemented.